2006
DOI: 10.1063/1.2165568
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating bead displacements in optical tweezers using acousto-optic deflectors

Abstract: Displacements of optically trapped particles are often recorded using back-focal-plane interferometry. In order to calibrate the detector signals to displacements of the trapped object, several approaches are available. One often relies either on scanning a fixed bead across the waist of the laser beam or on analyzing the power spectrum of movements of the trapped bead. Here, we introduce an alternative method to perform this calibration. The method consists of very rapidly scanning the laser beam across the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 31 publications
1
58
0
1
Order By: Relevance
“…Position detector calibration is achieved by moving the trapped bead through a known distance while recording the position signal. A bead, stuck to the surface of the trapping chamber, is moved with a calibrated piezo stage, or by scanning the trapping laser faster than the trapped bead can respond (see Box 1), thereby moving the laser with respect to the effectively stationary bead 55 . If an independent detection laser is employed, calibration can be performed by moving the bead through the detection laser by scanning the trap position 11 .…”
Section: Boxmentioning
confidence: 99%
“…Position detector calibration is achieved by moving the trapped bead through a known distance while recording the position signal. A bead, stuck to the surface of the trapping chamber, is moved with a calibrated piezo stage, or by scanning the trapping laser faster than the trapped bead can respond (see Box 1), thereby moving the laser with respect to the effectively stationary bead 55 . If an independent detection laser is employed, calibration can be performed by moving the bead through the detection laser by scanning the trap position 11 .…”
Section: Boxmentioning
confidence: 99%
“…와 갈바노 또는 압 (galvano) 전 기반의 구동기 및 (piezoelectric) (stage) AOD(Acousto-optic Deflector)를 이용하여 레이저 빔 경로를 빠르게 변조하는 주 사 레이저 광집게(SLOT, Scanning Laser Optical Tweezers) [5][6][7] 가 있다. …”
Section: 서 론 최근에 대두되고 있는 마이크로 나노 기술을 지속적으로unclassified
“…The acousto-optic effect is firstly proposed by Brillouin in 1922 [1] and experimentally demonstrated by Lucas and Biquard [2] in France, and Debye and Sears [3] in U.S. Much research work has been reported on the applications of AOD on frequency shifters [4], laser beam steering [5], imaging spectrometer [6], laser beam shaping [7], fringe projectors [8], multichannel communications [9] and optical tweezers [10]. The bandwidth and central frequency are the two most important design parameters of acousto-optic deflector, thus the comprehensive studies on the wideband operating mode are highly required for most applications.…”
Section: Introductionmentioning
confidence: 99%